Determination of Leading Fruit Commodities in the Horticulture Subsector in Gresik Regency - Rizqy, Mohammad; Setyadi, Taufik; Indah Harya, Gyska (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Agriculture remains a crucial sector as it is interconnected with various aspects, particularly the horticulture subsector, which is increasingly favored by farmers due to its relatively shorter harvest periods, especially for vegetables and fruits. This subsector holds a vital position as a promising agricultural product to be developed, and its growth is expected to boost the local economy and contribute to the Gross Regional Domestic Product (GRDP) of Gresik Regency. The government has prioritized the development of horticulture agribusiness, particularly fruit production, as it can enhance community income. This study aims to analyze the leading commodities in the fruit horticulture subsector that serve as base and non-base sectors in Gresik Regency, identifying their current and future positions. Using secondary data from the Central Bureau of Statistics, the study applies Location Quotient (LQ) and Delta Location Quotient (?LQ) methods to classify the potential of commodities into four categories: stars, mature, emerging, and transforming. Based on the analysis, water apple is identified as a "star" commodity, mango and rambutan fall into the "mature" category, starfruit, guava, pomelo, mangosteen, papaya, banana, soursop, and Breadfruit are in the "emerging" category. At the same time, avocado, durian, and mandarin orange are classified as "transforming" commodities. Contribution to Sustainable Development Goals (SDGs):SDG 1: No PovertySDG 2: Zero HungerSDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action